Examination of the usability of leaf chlorophyll content and gene expression analyses as nitrogen status biomarkers in Sorghum bicolor. (26th December 2020) - Rivai, Reza Ramdan; Takada, Rie; Miyamoto, Takuji; Hanano, Shigeru; Shibata, Daisuke; Ohdoi, Katsuaki; Kobayashi, Masaru
Abstract: Sorghum [ Sorghum bicolor (L.) Moench] has been receiving attention as a feedstock for biomass energy. Since nitrogen (N) significantly affects the plant biomass production, diagnosing the N status of sorghum during its growth would be significant. Therefore, in this study, we analyzed the changes in several physiological parameters of sorghum in response to N limitation, with the aim of identifying candidates of N status biomarkers in this species. Parameters responding early and sensitively to N deficiency were searched in hydroponically cultured seedlings, and their applicability to field conditions was examined. We found that the leaf chlorophyll content measured as a soil-plant analysis development (SPAD) value was promising as a candidate N status biomarker, as it showed responses consistent with N regimes in field conditions in multiple genotypes. A gene expression analysis was capable of detecting N deficiency sensitively at an early stage, although its application to practical situations requires further investigation to identify a suitable sets of marker genes.